KETIDAKPATUHAN ISTRI (WANITA KARIR) TERHADAP SUAMI ( SEBUAH PENDEKATAN HUKUM KELUARGA ISLAM ) - Arif Hariyanto; Halifatul Hasanah (Al-Hukmi : Jurnal Hukum Ekonomi Syariah dan Keluarga Islam, 2021)
Nusyuz is one of the themes discussed in the Quran. This study focuses on the disobedience of career women in the perspective of Islamic law which prioritizes justice and the relationship between husband and wife. It can be understood that nusyuz is an act of neglecting the obligations of husband and wife that causes estrangement of relations in the household with the provisions, nusyuz action is carried out with certain motives, and aims to degrade the dignity of one party. The more developed the situation, the more women's desire to move forward and develop their careers in the world of work. These working women are usually called career women, some of whom have different opinions regarding this, some allow it on conditions, and some do not absolutely allow it. The issue of women is indeed the most actual thing to talk about considering times have changed, the mindset of humans has also changed, in this modern era there are still people who look down on women, and discriminate against them. Although there are many who are interested in conducting research related to this case. The natural privileges possessed by men and women lead to differences in functions, and the main roles between the two. Islam obliges a man as a husband to provide for his wife and children, however, it does not necessarily rule out the possibility that a woman as a wife also earns a living to fulfill the family economy. Islam itself places men and women in a balanced and equal position. The problem behind the misunderstanding between the two is that there is a misunderstanding in constructing the social roles between men and women as a result of the interpretation of the Qur'anic text in particular and it seems incomplete. While basically the relationship between husband and wife, men and women is a partnership, which must support each other.